O alcance do artigo 444, parágrafo único, da CLT: preponderância do acordo individual sobre o instrumento coletivo - Carvalho, Leonardo da Costa (2023)
This work aims to discuss the scope of the sole paragraph of article 444 of the CLT, introduced with Law No. 13,467/2017, and which established a new factual reality for certain kind of employees, referred to as the “high ranked employee”. Employees covered by this condition have preponderance of negotiation powers over collective instrument. Thus, the legal requirements, the practical possibilities of this preponderance and autonomy over what can be negotiated will be studied, mentioning the position of the courts on the topic, especially the STF (Supreme Federal Court), which, albeit subtly, voiced its opinion during the covid-19 pandemic, authorizing individual negotiation of measures to preserve employment during the pandemic. Given the requirements of higher education graduation and the amount received as salary, this study seeks to assess whether such conditions are constitutional in light of the guarantees and principles of Labor Law